Tumour-cell-induced endothelial cell necroptosis via death receptor 6 promotes metastasis - Strilić, Boris; Han, Kang; Müller, Ulrike C. (Nature, 2016)
Human and murine tumour cells induce programmed necrosis (necroptosis) of endothelial cells, which promotes tumour cell extravasation and metastasis.